2017
DOI: 10.1177/1060028017738262
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anti-Xa Activity in Patients Receiving Apixaban or Rivaroxaban

Abstract: Good correlation was shown between anti-Xa activity and serum levels. The clinical utility of monitoring anti-Xa activity and the significance of the difference in trough anti-Xa activity for these agents remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…The institutional anti‐Xa used was a chromogenic assay (Diagnostica Stago S.A.S, Asniere sur Seine, France) with a hybrid validation curve for unfractionated heparin (UFH) and LMWH. The institution did not have FXa‐I‐specific assays available and the qualitative threshold of 0.5 units/ml was provided as institutional guidance based on prior literature 19–21 . The assay upper limit of detection was 1.8 units/ml while the lower limit was <0.1 units/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The institutional anti‐Xa used was a chromogenic assay (Diagnostica Stago S.A.S, Asniere sur Seine, France) with a hybrid validation curve for unfractionated heparin (UFH) and LMWH. The institution did not have FXa‐I‐specific assays available and the qualitative threshold of 0.5 units/ml was provided as institutional guidance based on prior literature 19–21 . The assay upper limit of detection was 1.8 units/ml while the lower limit was <0.1 units/ml.…”
Section: Methodsmentioning
confidence: 99%
“…While liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) is considered the gold standard for DOAC quantification, 22 it less likely to be available within on‐site hospital laboratories for monitoring patients. The anti‐Xa chromogenic assay, 3,23 which is commonly available in clinical laboratories and utilized within this study, has been shown to correlate to LC‐MS/MS 31 . Further correlations of the anti‐Xa assay calibrated for apixaban (ng/ml) versus heparin (IU) are presented in Figure S1.…”
Section: Discussionmentioning
confidence: 97%
“…12 The predicted peak and trough concentrations at steady state associated with <400 mg amiodarone 12 The anti-Xa chromogenic assay, 3,23 which is commonly available in clinical laboratories and utilized within this study, has been shown to correlate to LC-MS/MS. 31 Further correlations of the anti-Xa assay calibrated for apixaban (ng/ml) versus heparin (IU) are presented in to increased bleeding events. 67 While this study was designed to investigate DDIs within our patient population, the small sample sizes for each cohort limited the ability to delve into the impact of dose response for the P-gp and CYP3A4 inhibitors and precluded statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… äðóãîì ñëó÷àå àâòîðû ìåòîäèêè [12] ïðåäëàãàþò èñïîëüçîâàíèå ïðîáîïîäãîòîâêè, ïðåäïîëàãàþùåé äîïîëíèòåëüíîå ðàçáàâëåíèå îáðàçöà â 4 ðàçà, ÷òî ñíèaeàåò ÷óâñòâèòåëüíîñòü îïðåäåëåíèÿ.  ðàáîòå [13] äèàïàçîí îïðåäåëÿåìûõ êîíöåíòðàöèé ðèâàðîêñàáàíà ñîñòàâëÿåò 2 -500 íã/ìë, ÷òî ìîaeåò îêàçàòüñÿ íåäîñòàòî÷íûì ïðè ïðîâåäåíèè ÒËÌ. Àâòîðàìè ïðåäëîaeåíà ïðîñòàÿ è áûñòðàÿ àíàëè-òè÷åñêàÿ ìåòîäèêà (âðåìÿ àíàëèçà 3 ìèí), ÷òî äîñòèãàåòñÿ áëàãîäàðÿ èçîêðàòè÷åñêîìó ýëþèðîâàíèþ.…”
unclassified